KRATON: MENJAGA PEREMPUAN, MENJAGA KEBUDAYAAN (STUDI KASUS ABDI-DALEM PEREMPUAN KRATON KASUNANAN SURAKARTA) - Astuti, Riandini Tri; Pratama, Yogi Pasca (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
The study of women has always attracted the attention of a variety of multi-disciplines. This paper examines women from the discipline of economics which is supported by the study of other sciences, especially gender and culture. This paper describes how the Kraton, as the center of Javanese culture, contributed to keeping women and culture. Thesis writing material adapted from the author himself in 2015, which was then coupled with studies of secondary data as a complement and a reformer. The object of research was the Women Abdi-Dalem Kraton Surakarta, the focus is on the family breeds servants Abdi-Dalem Mbah Dullah , as the only breed longest tradional family servants, namely 5 generations. The object of the research proposed by the Kraton Surakarta appropriate to the purpose of the author, which focus more on parenting and sustainability of the Abdi-Dalem. Keywords: Abdi-Dalem, Gender, and CultureJEL Classification: A13, B54, Z00